Penelitian Kualitatif Sistem Kerja Berkinerja Tinggi pada Kelompok Usaha Otomotif di Sulawesi Selatan - I Wayan Gede Suharta Dewantara; Eka Afnan Troena; Siti Haerani; Nurdjanah Hamid (Hasanuddin Journal of Business Strategy, 2019)
Although there are often family businesses or family-based companies in Indonesia, qualitative researches on this topic, linked to leadership and high-performance work systems, are still very rare. For this reason, the goal of the research is to find out how transformational leadership and high-performance work systems are used in the company's day-to-day operations to achieve the company's performance results. This study was conducted in a group of family business companies in South Sulawesi. The company group has an agenda to deliver the best corporate values, including leadership practices and high-performance work systems. With the help of the questionnaires distributed in the company environment, 3000 responses were received and treated with content analysis. The encoding processes in the text analysis revealed that the company has implemented transformation management with the highest level of visibility, strategy, and performance. For a high-performance work system, the company has done well and is less dependent on enterprise management and managers can use the results of this research to improve management practices and high-performance work systems that are better for employees.